A Comparative Analysis of Experimental Research Designs: Pre-Experimental, Quasi-Experimental, and True Experimental in the Development of Islamic Religious Education Research - Tedi Priatna; Bayu Bambang Nurfauji; Eli Setia Mukti Sari; Nia Nurmalasari; Shannaz Syahida Fadhilah Andhini (Penerbit Hellow Pustaka, 2026)
This study aims to comparatively analyze experimental research designs, namely Pre-Experimental Design, Quasi Experimental Design, and True Experimental Design, in the development of Islamic Religious Education (IRE) research. The method employed is a library research approach using descriptive-comparative analysis of relevant books, scientific articles, and academic references. The analysis focuses on the characteristics, strengths, weaknesses, validity levels, and applications of each experimental design in IRE research. The findings indicate that Pre-Experimental Design is suitable for preliminary studies with limited control over variables, although it has low internal validity. Quasi Experimental Design provides a balance between research control and real educational settings, making it widely used in educational research. Meanwhile, True Experimental Design offers the highest level of internal validity through the implementation of randomization and strict control groups. In conclusion, the selection of an experimental design in Islamic Religious Education research should be adjusted to research objectives, participant conditions, and available resources in order to produce valid, reliable, and meaningful findings for the advancement of IRE studies.